Distributed Preemptive Process Management With Checkpointing And Migration For A Linux-Based Grid Operating System - Htin, Paw Oo @ Nur Hussein (2006)

(untitled)
Kemunculan perkomputeran grid telah membolehkan perkongsian sumber perkomputeran teragih antara peserta-peserta organisasi maya. Walau bagaimanapun, sistem pengoperasian kini tidak memberi sokongan paras rendah secukupnya untuk perlaksanaan perisian grid. Kemunculan suatu kelas sistem pengoperasian yang dipanggil sistem pengoperasian grid memberikan pengabstrakan peringkat sistem untuk sumber-sumber grid The advent of grid computing has enabled distributed computing resources to be shared amongst participants of virtual organisations. However, current operating systems do not adequately provide enough low-level facilities to accommodate grid software. There is an emerging class of operating systems called grid operating systems which provide systemslevel abstractions for grid resources.